(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The aim of the current research is to know the expressive performance and its importance in the intermediate stage, and to know the importance of expressive performance in the intermediate stage. To achieve the goal of the research, the researcher followed the procedures of the descriptive approach. The researcher prepared a questionnaire on the topics of expression, which was presented to a group of experts and arbitrators in the field of curricula, teaching methods, educational psychology, and measurement.